Peran profitabilitas dalam memediasi leverage dan total asset turnover tehadap beta saham - Wahyuningsih, Wahyuningsih; Nabhan, Faqih (Journal of Accounting and Digital Finance, 2022)
This study aims to determine the effect of leverage and total asset turnover on stock beta with profitability as an intervening variable in companies listed on the Jakarta Islamic Index 70 (JII70) for the 2018–2020 period with a sample of 38 companies taken based on purposive sampling technique. The analysis used includes descriptive tests, classical assumption tests, hypothesis testing, and path analysis. The results of the analysis show that the leverage variable has a significant positive effect on stock beta. while the variables of total asset turnover and profitability have no effect on stock beta. And in the path analysis, it is known that the effect of leverage and total asset turnover on stock beta cannot be mediated by the profitability variable.